Clinical presentation of incidentally discovered adrenal tumors ‒ our experience - Dragović, Tamara; Mitrović-Jovanović, Valentina; Kiković, Saša; Kuzmić-Janković, Snežana; Ristić, Petar; Karajović, Jelena; Đuran, Zorana; Marinković, Dejan M; Hajduković, Zoran (Vojnosanitetski pregled, 2021)
Background/Aim. Incidentalomas of the adrenal gland are adrenal masses commonly discovered by chance on imaging not performed for suspected adrenal disease. The aim of this study was to analyze clinical, hormonal and histopathological characteristics of adrenal incidentalomas. Methods. This retrospective study included 85 patients (32 men and 53 women) examined for adrenal incidentalomas at the Clinic for Endocrinology, Military Medical Academy in Belgrade, from January 2013 to December 2017. The age of the patients, gender, size, and localization of adrenal tumors, functional activity, as well as the presence of comorbidities were analyzed. Adrenalectomy was performed in 35 patients due to its size and functional activity, and histological findings were analyzed. Results. The largest number (56.4%) of the adrenal tumors, was detected by ultrasound examination of the abdomen, 23 (27.2%) by abdominal computed tomography (CT) scan, 13 (15.2%) by chest CT scan and 1 (1.2%) by magnetic resonance (MR) imaging of the abdomen. The average tumor size was 3.8 ± 2.3 cm (range from 1 to 15 cm). Adrenal tumors were bilateral in 20 (23%) patients, in 39 (46%) patients, the tumors were localized in the right adrenal gland, and in 26 (31%) in the left gland. Subclinical hypercortisolism, defined as insufficient cortisol suppression during overnight dexamethasone test (1 mg), was observed in 34 (40%) patients, while the absence of cortisol suppression (autonomous cortisol secretion) was found in 4 (4.7%) patients. In the remaining 47 (55.3%) patients, complete overnight suppression of cortisol secretion was achieved. Thirty-five (41%) patients underwent adrenalectomy; among them, in 4 (11.4%) cases, adrenocortical carcinoma was found, 15 (42.9%) were adenomas, pheochromocytoma was found in 4 (11.4%) cases, nodular hyperplasia in 5 (14.3%) cases, distant metastasis in one (2.8%) case and the remaining were different benign masses. Conclusion. For patients with adrenal incidentalomas, two fundamental questions on determining the functionality of the tumor and/or the presence of malignancy need to be clarified. All patients with adrenal incidentaloma should undergo hormonal evaluation for autonomous or possible autonomous cortisol secretion, as well as for autonomous, adrenergic, and mineralocorticoid excess. In patients with autonomous adrenal secretion, surgery is indicated even if the typical clinical manifestation is absent.